2008
DOI: 10.1016/j.rmed.2008.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological features of Mycobacterium kansasii infection and Mycobacterium simiae infection

Abstract: This retrospective study sought to systematically identify clinical and radiological features of Mycobacterium kansasii and Mycobacterium simiae infections. The sample included consecutive patients with a culture-positive diagnosis of M. simiae infection (n=102) or M. kansasii infection (n=62) derived from the databases of the Laboratory of Microbiology of a tertiary medical centre and two outpatient tuberculosis centres. Data on patient background and clinical features were collected, and chest radiographs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 24 publications
(24 reference statements)
1
42
3
Order By: Relevance
“…The commonly reported symptoms are productive cough, dyspnea, malaise, fever, sweat, and body weight loss (9). The lack of respiratory symptoms and the negative findings of chest radiographs suggest that our patient may have had long-term M. simiae colonization, which subsequently developed into multilobar pneumonia.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…The commonly reported symptoms are productive cough, dyspnea, malaise, fever, sweat, and body weight loss (9). The lack of respiratory symptoms and the negative findings of chest radiographs suggest that our patient may have had long-term M. simiae colonization, which subsequently developed into multilobar pneumonia.…”
mentioning
confidence: 74%
“…Clinical M. simiae isolation is usually from respiratory specimens, and most of them are from patients with AIDS, cancer, or chronic obstructive pulmonary disease (1). The clinical relevance of M. simiae isolation from respiratory specimens either as a colonizer of the respiratory tract or as a true pathogen causing pneumonia ranged from 9% to 24% (9,11). In our patient, M. simiae was recovered from multiple respiratory secretion specimens during hospitalization.…”
mentioning
confidence: 99%
“…Recently, this organism has been widely reported from other areas, including the Middle East (6)(7)(8)(9). Transmission of M. simiae to humans and possible environmental sources of this organism remain unclear; however, the routes of entry are probably respiratory and digestive tracts (10).…”
Section: Introductionmentioning
confidence: 99%
“…M. simiae infections have been found in various regions such as the southern United States, Israel, and Cuba [6][7][8][9][10]. The infections are most commonly found in immunosuppressed hosts such as HIV-positive individuals, the elderly, children, and those with a history of tuberculosis (TB) [6,[11][12][13]. Furthermore, those with other diagnosed diseases such as diabetes mellitus, cardiovascular disease, and malignancy are more prone to acquiring M. simiae infection [11].…”
Section: Introductionmentioning
confidence: 99%
“…simiae can cause infections in diverse organs, especially in the respiratory system, causing variable clinical manifestations. A recent study indicated that individuals of certain ethnic origins, particularly those from the Middle East region, seemed to be more prone to contracting the disease [11].Only a few cases of M. simiae infections have been documented, and there is only one established case report of M. simiae in Iran [14].…”
Section: Introductionmentioning
confidence: 99%